Evaluation of Natural and Chemical Coagulants Performance in Treatment of Municipal Wastewater of Behshahr City - Sakineh Tabaki; Fatemeh Ardestani (Hamadan University of Medical Sciences, 2021)
Municipal wastewater is one of the largest volumes of wastewater which contains various organic compounds from proteins and fats to carbohydrates and nucleic acids. Municipal wastewater of Behshahr city (Mazandaran, Iran) was evaluated using aluminum sulfate and iron chloride as chemical coagulants and pectin and sodium alginate as natural ones. Biological oxygen demand was investigated at different temperatures and coagulant concentrations. The fraction of full factorial statistical method and Qualitek-4 software were applied for designing experiments and analyzing the results to determine the optimal conditions for achieving the highest reduction in wastewater organic load and biological oxygen demand. In the case of biological oxygen demand, the optimal condition was achieved at 25°C, using 1, 0.02, 1.5 and 1 g/L of aluminum sulfate, sodium alginate, iron chloride and pectin, respectively. Under the optimal condition, the percentage of biological oxygen demand reduction was equal to 34.5%. Maximum BOD removal of 40.9% was obtained at 25°C using aluminum sulfate, sodium alginate, iron chloride, and pectin at concentrations of 0.6, 0.02, 1.5, and 6 g/L, respectively. The contribution of aluminum sulfate, sodium alginate, iron chloride, and pectin concentration in biological oxygen demand removal of the studied wastewater was 3.8%, 22.4%, 16.3%, and 14.4%, respectively. Coagulation temperature and aluminum sulfate concentration with approximately 42.7% and 3.8% contribution values were determined as the most and the least effective factors in biological oxygen demand reduction.